2022
DOI: 10.1038/s41598-022-11081-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between anion gap and in-hospital mortality of post-cardiac arrest patients: a retrospective study

Abstract: We aimed to determine the association between anion gap and in-hospital mortality in post-cardiac arrest (CA) patients. Extracted the data of patients diagnosed with CA from MIMIC-IV database. Generalized additive model (GAM), Cox regression and Kaplan–Meier survival analysis were used to demonstrate the association between AG levels and in-hospital mortality. ROC curve analysis for assessing the discrimination of AG for predicting in-hospital mortality. Totally, 1724 eligible subjects were included in our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…The relationship between elevated serum AG levels and the prognosis of associated disorders has recently been supported by numerous studies 6–14 . High serum AG levels were discovered to be an independent risk factor for death at 30 d and 90 d in patients with congestive heart failure in a recent study by Tang Y et al 25 utilizing data from the MIMIC‐III database.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The relationship between elevated serum AG levels and the prognosis of associated disorders has recently been supported by numerous studies 6–14 . High serum AG levels were discovered to be an independent risk factor for death at 30 d and 90 d in patients with congestive heart failure in a recent study by Tang Y et al 25 utilizing data from the MIMIC‐III database.…”
Section: Discussionmentioning
confidence: 92%
“…24 The relationship between elevated serum AG levels and the prognosis of associated disorders has recently been supported by numerous studies. [6][7][8][9][10][11][12][13][14] High serum AG levels were discovered to be an independent risk factor for death at 30 d and 90 d in patients with congestive heart failure in a recent study by Tang Y et al 25 utilizing data from the MIMIC-III database. Similar results were reported in a study by Gong Y et al 26 who discovered a non-linear, U-shaped relationship between AG levels and 30-day all-cause mortality in AKI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a traditional index of acid-base balance, AG may be a prognostic maker to predict outcomes. Previous studies demonstrated that AG was related to mortality of many cardiovascular diseases ( 6 , 9 , 15 ) and patients with elevated AG showed worse cardiac ( 16 ) and renal functions ( 17 ). These evidences suggested that AG might be an indicator of severe disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative acid-base imbalance and electrolyte disturbances are common in patients who underwent cardiac surgery ( 18 ). Under cardiopulmonary bypass, hypoxia, ischemia, and acidosis occur frequently, which promote increased acidic substance and thus elevate AG levels ( 15 ). AG may indicate the status of hypoperfusion by reflecting the cumulative levels of acidic substance due to ischemia; while hemodynamic instability like hypotension is demonstrated to be associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%